DEVELOPING LEARNING MEDIA THROUGH MACROMEDIA FLASH APPLICATION FOR ENGLISH PHONOLOGY CLASS - Deiniatur, Much (JURNAL SMART, 2019)
The purpose of this study is to develop a learning media model using the Macromedia Flash application to be used in English Phonology learning and to determine the feasibility of appropriate Macromedia Flash-based learning media to support English Phonology learning. This research is a Research and Development Research (R & D) with stages (1) Stages of Analysis, namely Identifying the objectives of Learning Media and Identifying Student Characteristics; (2) Design Stages, namely Designing learning materials and Designing learning media design using the Macromedia Flash program; (3) Production stages, namely Producing learning materials, Authoring materials, and Editing learning materials; (4) Evaluation Stages, namely Material Expert Review, Media Expert Review, and Test on students.The results show that the English Phonology learning media products have met the rules of research and development and are effectively used in the learning process for Students of the English Language Department of IAIN Metro Lampung.